2006
DOI: 10.1002/jlcr.1084
|View full text |Cite
|
Sign up to set email alerts
|

Role of protecting groups in the preparation of thiolate complexes of technetium-99 m using cysteine as a model

Abstract: SummaryAn attempt has been made to develop a suitable protecting group for the thiolate function for 99m Tc binding ligands having such function and which could be deprotected automatically during Tc-chelation without the use of any additional reagents. As a model ligand a simple molecule like l-cysteine was selected. Seven S-protected derivatives of this amino acid were synthesized, radiolabelled with technetium-99 m under a variety of experimental conditions and the yield of the desired chelate was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Disulfide bonds contribute to protein folding and their conformational stabilities as well as their general functions ( Roy et al, 2006 ; Chatterjee Debnath et al, 2010 ; Roy and Luck, 2011 ). 1J0S and 3WO2 have four Cys residues (38, 68, 76 and 127), while none of them forms disulfide bridges ( Yamamoto et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Disulfide bonds contribute to protein folding and their conformational stabilities as well as their general functions ( Roy et al, 2006 ; Chatterjee Debnath et al, 2010 ; Roy and Luck, 2011 ). 1J0S and 3WO2 have four Cys residues (38, 68, 76 and 127), while none of them forms disulfide bridges ( Yamamoto et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we have attempted to develop a suitable –SH protecting group for thiolate function, and the S ‐thiomethyl (−SCH 3 ) group was proved to be the most successful in this regard. S ‐thiomethyl protection was well studied in cysteine and l , l ′‐EC; thiomethylated precursor of both the ligands produced the desired technetium chelate in quantitative yield . In the present study, we describe the method of thiol protection during technetium chelation of DMSA and ECD.…”
Section: Discussionmentioning
confidence: 95%
“…The shelf life of both DMSA and ECD kit can be enhanced by suitable protection of the thiolate functionality. In our ongoing study programme, we already developed S ‐thiomethyl as a novel thiol‐protecting group and used to protect the thiol functionality of l ‐cysteine . We also reported that protection of the thiol function of l , l ′‐ethylene dicysteine ( l , l ′‐EC) by S ‐thiomethylation allows automatic deprotection during 99m Tc chelation without the use of any additional reagents.…”
Section: Introductionmentioning
confidence: 99%
“…S ‐benzoyl mercaptoacetyltriglycine ( 1 ) was prepared as per the reported method . Methylsulphenyl chloride was prepared by following the procedure described by us . HPLC analysis were performed on a reverse phase C‐18 column (4.6 × 250 mm, particle size 5 µm) fitted to a Waters Associates HPLC system (Waters Corporation, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In the course of our study, S ‐thiomethyl (–S‐CH 3 ) has been developed as a sulfhydryl protecting group and was well studied on different technetium binding –SH containing ligands, for example, cysteine, L,L′‐EC, Dimercaptosuccinic acid and others . In this study, we report the protection of the thiol function of MAG 3 by S ‐thiomethylation that could be deprotected automatically during technetium‐99m labelling at relatively mild reaction condition.…”
Section: Introductionmentioning
confidence: 95%